The Catholic Movement of Employers and Managers - Dion, Gérard (Relations industrielles / Industrial Relations, 1962)
The article reviews the book, "The Catholic Movement of Employers and Managers," by Joseph B. Gremillon. Published by Gregorian University Press, 4 Piazza della Pilotta, Rome, 1961.